Korpusna lingvistika kao osnovna paradigma istraživanja jezika (Philologia, 2021)
The introspection–based analysis has been the prevailing linguistic paradigm for a long time. The corpus approach in its contemporary framework marks the return of linguistics within the boundaries of empirically founded sciences, where a scientific discipline which studies language surely does belong. This paper first elaborates on the advantages of such a research approach which focuses on the language community using a given language and the nuances of their usage. The paper goes on to describe the basic characteristics of the corpus approach to linguistics. In the end the paper stresses the importance of constructing a general representative computer corpus of the Serbian language.
Keywords: korpus; diskurs; frekventnost; token; konkordanser; statistika